The Anomie of the Earth : Philosophy, Politics, and Autonomy in Europe and the Americas - Kaiser, Wilson, 1978-; Pickles, John, 1952-; Luisetti, Federico, 1969- (Book collections on Project MUSE., 2015)
The contributors to The Anomie of the Earth explore the convergences and resonances between Autonomist Marxism and decolonial thinking. In discussing and rejecting Carl Schmitt's formulation of the nomas-a conceptualization of world order based on the Western tenets of law and property-the authors question the assumption of universal political subjects and look toward a politics of the commons divorced from European notions of sovereignty. They contrast European Autonomism with North and South American decolonial and indigenous conceptions of autonomy, discuss the legacies of each, and examine social movements in the Americas and Europe. Beyond orthodox Marxism, their transatlantic exchanges point to the emerging categories disclosed by the collapse of the colonial and capitalist frameworks of Western modernity.